Diagnostic utility of Sudoscan for detecting bortezomib-induced painful neuropathy: a study on 18 patients with multiple myeloma - Alessandro Allegra; Vincenzo Rizzo; Vanessa Innao; Angela Alibrandi; Anna Mazzeo; Rossana Leanza; Carmen Terranova; Luca Gentile; Paolo Girlanda; Andrea Gaetano Allegra; Andrea Alonci; Caterina Musolino (Archives of Medical Science, 2021)
Introduction In the past few years, treatment of multiple myeloma has undergone a deep change for the employment of novel treatment comprising proteasome inhibitors. Bortezomib is a first-line drug in therapy of multiple myeloma. The onset of peripheral neuropathy is a dose-limiting collateral effect of the drug. This neuropathy is a distal symmetric neuropathy that affects both large and small fibers. Nerve conduction study (NCS) can be used for the diagnosis of bortezomib neuropathy, but this technique demonstrates alterations of the large nerve fibers. Sudoscan is a novel technique utilized to offer an evaluation of sudomotor function. The main objective of this study was to compare the sensitivity and diagnostic specificity of Sudoscan with respect to the nerve conduction study after bortezomib treatment.